Endocrine Referral Pattern: Experience From a Medical College Hospital: Endocrine Referral Pattern from a Medical College Hospital - Hasan, Md Rakibul; Akther Mou, Sayma; Mozaffor, Miliva (Journal of the Medical College for Women & Hospital, 2025)
Background: Referral is an integral part of comprehensive disease management, particularly when it involves multiple complications and comorbidities. Data regarding the referral pattern of endocrine diseases are scarce in the literature, especially from Bangladesh. Aim: To find out the referral patterns and spectrum of endocrine diseases among the referred patients. Materials and Method: This retrospective observational study included all consecutive patients who were referred to the endocrinologist from March 2022 to October 2024. Relevant clinical information of the referred patients was extracted from the referral registrar book. Results: A Total of 759 patients (Male 185, 24.4%; Female 574, 75.6%; median age 45 years were included in the study. The majority of the patients were referred from the inpatient department (IPD) (428, 56.4%). Medicine and allied departments were the main source (303, 39.9%) of referrals, followed by Surgery (240, 31.6%), Gynecology (204, 26.9%), and others (12, 1.6%). The majority of the patients suffered from multiple active non-endocrine diseases (≥two diseases, 651, 85.7%); however, most of the patients were referred for a single endocrine disease (640, 84.3%). Among the endocrine causes of referral, diabetes mellitus (DM) (612, 80.6%) was the most common cause of referral, followed by thyroid disorder (TDs) (152, 20%). Among referred patients with DM, multiple endocrine diseases were present in 97(15.8%) cases, and TDs were present in 60 (9.8%). Among other endocrine referrals, reproductive endocrine disease, adrenal disease, and electrolyte imbalance accounted for 32 (4.2%), 23 (3.0%), and 35 (4.6%), respectively. Conclusion: DM and TDs are the two most common forms of referral, followed by reproductive endocrine disease and adrenal disease, with more than half of the referred patients from IPD. J Med Coll Women Hosp.2025; 21 (2):62-70